Shrimp Pond Business Local Market Strenghthening: An Initiation - Anthon Efani; Nuddin Harahab; Mimit Primyastanto; Edi Susilo; Wahyu Handayani (Wacana Journal of Social and Humanity Studies, 2020)
This research is conducted to provide strategies to strengthen the local market shrimp commodity. The method used in this research is qualitative descriptive and obtain the data by Focus Group Discussion (FGD) and structured interviews. The results show that the need for export, shrimp is generally obtained from cultivation in ponds. Shrimp dominates more than 40% of fishery products for export and earn foreign exchange. During the COVID-19 pandemic, it is necessary to strengthen marketing in the local market to minimize the impact of barriers to export shrimp abroad. Several things can be done to strengthen the local market, among others, conduct a shrimp consumption campaign, increase value-added of processed shrimp product, implement shrimp farming method using small-scale round ponds for the community for marketing efficiency. This is done to ensure shrimp supply in the market in accordance with the market demand. Finally, these strategies can create an integrated local market system for shrimp commodities, so that it can provide not only the international market but also the local market.